The relationship of chronic obstructive pulmonary disease and coronary heart disease: problems of pathogenesis and treatment strategy - Yatsenko, O. V. (Zaporozhye Medical Journal, 2014)
Aim. The article presents a review of the literature on comorbidity of chronic obstructive pulmonary disease and coronary heart disease on the occurrence, pathogenetic connection with clinical manifestations. Methods and results. This article analyzed the prevalence of the combination of these diseases, suggesting an important role of the clinician in a timely diagnosis to improve their pharmacotherapeutic approach, management of patients. Also provides an overview of the pathogenetic link between chronic obstructive pulmonary disease and coronary heart disease.